Kontekstulisasi Dan Reposisi Fungsi Wakaf Dalam Upaya Meningkatkan Kesejahteraan Umat - Moh. Subhan (JES (Jurnal Ekonomi Syariah), 2018)
The discourse on waqf recently appears the back to the surface. It not only discusses about the opinion of the fiqh scholars who have no uniform about understanding and nature waqf  itself, but also to reform and optimize waqf  in order to do more, namely to superintend the social problems of society, related to the prosperity of the economy of the people. Therefore, contextualization and repositioning of waqf institutions becomes a necessiry for immediate implementation. The function and role of waqf is very large in supporting the development and progress of the muslims. Therefore the management of waqf must be able to be optimized. Tragically the management of waqf in Indonesia is still not maximized, so there are some waqf property abandoned in its management, some even missing. This is due to the waqf management still uses traditional-consumptive management pattern. Efforts to develop waqf to be productive and productive, there are four things to note; Institutional aspect, accounting aspect, auditing aspect and aspect of nadhir. If these four aspects can be met, then the utilization of waqf will be more efficient. There are several forms of models that can be run by the manager of waqf, such as by holding Sharia banks as a partner with schema of murabahah, istisna’, ijarah muntahiyah bi al-tamlik (financial leasing with purchase option), muzara’ah, qard al-hasan, musharakah (partnership) and mudarabah muqayyadah. Keywords: Contextualization, Repositioning of Waqf, Prosperity of the People